Nilai-Nilai Pendidikan Karakter dalam Syair Zuhdiyât Karya Abu Al-‘Atâhiyah - Kasim Yahiji; Damhuri Damhuri (Al-Ulum, 2014)
Discourse of the implementation of character values on the National Educational System is not a new agenda. The implementation has motivated by the national awareness about the importance of character building toward the young generation as the guarantees for nation strength. The aim is to improve students’ potency and build them to be piety to Allah SWT, to have good personality, to be healthy, intellectual, smart, and creative, be autonomous, and become democratic citizen, responsible, in accordance with the message on the law of National Education system. It is indicated that the first value should be implemented is universal truth without formulating the source. Literature works is one of sources which full of moral teaching and can be analyzed to find out the truth, and transferred to the students. The values of educational character on literature work can be implemented to students through emotional analysis. Abu al-‘Atâhiyah poems is one of literary works which full of moral teaching and can be analyzed and implemented on education, both formal and non-formal schools.